PUBLIC VERSUS PRIVATE BROADCASTERS' MANAGEMENT. Issue 8 (20th August 2014) - Vila, Natalia; Kuster, Ines
Abstract : Purpose: To prove the existence of significant differences between private and public corporate credibility antecedents and effects. Design/methodology/approach: 816 Spanish viewers' valuations were obtained (408 for the public television network and 408 for four private first generation broadcasters). Results show that some corporate reputation antecedents (perceived quality) and effects (attitudes) are stronger when private broadcasters are considered. Findings: Result show that proposed credibility reputation antecedents and effects are significant and that some differences between private and public entities really do exist. Practical implications: Theoretical/Academic Implications: the general impressions subsumed under the concept of corporate credibility are used to easily and automatically evaluate particular offers. Practitioner/Policy Implications: to enhance a television network's reputation managers can follow two different but related paths: improve the quality and improve the consistency of the network's visual identity. That is, they should act on both content and form. However, public or private commercial broadcasters should emphasize different ways. Originality/value: Show, in the broadcasting industry, that new challenges and responsibilities for public broadcasting services in this new digital era of liberalization do really exist compared to private companies.